A Study of Risk Management in the Faculty of Education Mahachulalongkornrajavidyalaya University - ชัยสุข พีรวัฒน์; โอภาโส พระครูโอภาสนนทกิตติ์ (Journal of Educational Review Faculty of Education in MCU, 2018)
The purpose of this research was to study the levels of risks and to create a guideline in risk management in the Faculty of Education, Maha chulalongkornrajavidyalaya University. The data were collected from documents and interview in 6 items of risk management. The data were analyzed by means (X), standard deviation (S.D.) and content analysis. It was found that: 1. All 6 items in risk management of the Faculty of Education, Mahachulalongkornrajavidyalaya University: finance, strategy, management, technology and communication, teaching and learning, and educational confidence were at the low level. 2. The comments and suggestions about the management risk, there should be ways in managing factors and controlling business operation to reduce the causes of each chance in damaging or lacking of efficiency. The risk in finance and teaching and learning should be reduced to an acceptable level of risks and a size of the damage.